3D game-based learning music theory with augmented reality (AR) - Cheng, Wong See; Rassem, Taha Hussein (2021)
Music theory is a kind of difficult course since its logic is biased towards art, and most people cannot measure and understand it with normal logical thinking, thus, most of them will encounter problems in the process of learning music, especially children. This application applies 3D game-based learning with Augmented Reality (AR) and a book tutorial with this application for scanning used. It aims to design new music learning application that helps to attract the children to learn and can be more impressive and firming in music theory. Music topic covers on notes name, notes value, time signatures, clefs, music terms, and performance direction. AR technology is used for the learning part (with book), while the game part is an escape game with quizzes to determine the children's level of understanding. The innovation in the project is to improve the effectiveness and performance of children's learning processes and reduce family burden.